Puzzling Over the Pneumococcal Pangenome - Hiller, N. Luisa; Sá-Leão, Raquel (Frontiers in Microbiology, 2018)
The Gram positive bacterium Streptococcus pneumoniae (pneumococcus) is a major human pathogen. It is a common colonizer of the human host, and in the nasopharynx, sinus, and middle ear it survives as a biofilm. This mode of growth is optimal for multi-strain colonization and genetic exchange. Over the last decades, the far-reaching use of antibiotics and the widespread implementation of pneumococcal multivalent conjugate vaccines have posed considerable selective pressure on pneumococci. This scenario provides an exceptional opportunity to study the evolution of the pangenome of a clinically important bacterium, and has the potential to serve as a case study for other species. The goals of this review are to discuss pneumococcal genomic diversity and plasticity, and highlight general principles and exciting open questions in the context of bacterial biology and evolution.